A multivariate analysis of women's mating strategies and sexual selection on men's facial morphology. Issue 1 (15th January 2020) - Clarkson, Tessa R.; Sidari, Morgan J.; Sains, Rosanna; Alexander, Meredith; Harrison, Melissa; Mefodeva, Valeriya; Pearson, Samuel; Lee, Anthony J.; Dixson, Barnaby J. W.
Abstract : The strength and direction of sexual selection via female choice on masculine facial traits in men is a paradox in human mate choice research. While masculinity may communicate benefits to women and offspring directly (i.e. resources) or indirectly (i.e. health), masculine men may be costly as long-term partners owing to lower paternal investment. Mating strategy theory suggests women's preferences for masculine traits are strongest when the costs associated with masculinity are reduced. This study takes a multivariate approach to testing whether women's mate preferences are context-dependent. Women ( n = 919) rated attractiveness when considering long-term and short-term relationships for male faces varying in beardedness (clean-shaven and full beards) and facial masculinity (30% and 60% feminized, unmanipulated, 30% and 60% masculinized). Participants then completed scales measuring pathogen, sexual and moral disgust, disgust towards ectoparasites, reproductive ambition, self-perceived mate value and the facial hair in partners and fathers. In contrast to past research, we found no associations between pathogen disgust, self-perceived mate value or reproductive ambition and facial masculinity preferences. However, we found a significant positive association between moral disgust and preferences for masculine faces and bearded faces. Preferences for beards were lower among women with higher ectoparasite disgust, providing evidence for ectoparasite avoidance hypothesis. However, women reporting higher pathogen disgust gave higher attractiveness ratings for bearded faces than women reporting lower pathogen disgust, providing support for parasite-stress theories of sexual selection and mate choice. Preferences for beards were also highest among single and married women with the strongest reproductive ambition. Overall, our results reflect mixed associations between individual differences in mating strategies and women's mate preferences for masculine facial traits.